Mproving Explanatory Text Reading Skills Through Natural Phenomenon Video-Assisted Inquiry Method In Students - Syaharuddin M, Rabiah; Syamsi, Kastam (UNIVERSITAS PAKUAN, 2025)
This research aims to improve the quality of the learning process of reading explanatory texts and improve the skills of reading explanatory texts in students of class XI TKR SMK Negeri 2 Tarakan. This research is a classroom action research. The subject of this study is students of class XI TKR SMK Negeri 2 Tarakan in the even semester of the 2023/2024 academic year. The implementation and implementation procedures at the research site consist of two cycles. In cycles I and II, two meetings were held. The activities of each cycle include: planning, implementation, observation, and reflection. Data was obtained with instruments in the form of: student activity observation sheets, teacher activity observation sheets, field notes, interview guidelines, documentation, and tests. The analysis techniques in this study include the process and results of classroom actions that are carried out in a descriptive, qualitative, and quantitative manner. The success rate of the process if in this study there is a change in improving the quality of the learning process. The success rate of the product is achieved if each student experiences an increase in the score of observation results and assessment of explanatory text reading skills through the inquiry method assisted by natural phenomena video. The results of the study showed that there was an improvement in the quality of the learning process of explanatory text reading skills and explanatory text reading skills of students in class XI TKR SMK Negeri 2 Tarakan even semester of the 2023/2024 school year through the application of the natural phenomenon video-assisted inquiry method. The improvement of explanatory text reading skills can be seen in the average score of the results of the ability to read explanatory texts from the pre-action stage, cycle I, and cycle II. The average score in the pre-action was 68.53. In the first cycle, the average score was 70.15, and in the second cycle, the average score was 79.71